Collaboration between dermatologists and dentists in autoimmune bullous diseases and immunoglobulin A antibodies in pemphigus. (3rd August 2016) - Hashimoto, T.
Abstract : Linked Article: Ali et al. Br J Dermatol 2016; 175 :113–121 .